2011
DOI: 10.1093/cid/cir025
|View full text |Cite
|
Sign up to set email alerts
|

Containment of a Country-wide Outbreak of Carbapenem-Resistant Klebsiella pneumoniae in Israeli Hospitals via a Nationally Implemented Intervention

Abstract: A centrally coordinated intervention succeeded in containing a nationwide CRE outbreak after local measures failed. The intervention demonstrates the importance of strategic planning and national oversight in combating antimicrobial resistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
351
1
15

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 396 publications
(378 citation statements)
references
References 35 publications
11
351
1
15
Order By: Relevance
“…CPE have been implicated in hospital outbreaks and have the propensity to spread (or disseminate their plasmids) rapidly at local, regional, and international levels. [10][11][12][13][14][15] We provide comprehensive survey results on the occurrence of carbapenemase-producing K pneumoniae and E coli between Nov, 2013, and April, 2014, from 455 hospitals in 34 European countries plus Turkey and Israel, together serving more than 270 million citizens out of a total population of 600 million. During the course of this investigation, NELs successfully expanded their capacity and adjusted workfl ows to accommodate new diagnostic tests.…”
Section: Discussionmentioning
confidence: 99%
“…CPE have been implicated in hospital outbreaks and have the propensity to spread (or disseminate their plasmids) rapidly at local, regional, and international levels. [10][11][12][13][14][15] We provide comprehensive survey results on the occurrence of carbapenemase-producing K pneumoniae and E coli between Nov, 2013, and April, 2014, from 455 hospitals in 34 European countries plus Turkey and Israel, together serving more than 270 million citizens out of a total population of 600 million. During the course of this investigation, NELs successfully expanded their capacity and adjusted workfl ows to accommodate new diagnostic tests.…”
Section: Discussionmentioning
confidence: 99%
“…Corrado Girmenia, 1 Claudio Viscoli, 2 Alfonso Piciocchi, 3 Laura Cudillo, 4 Stefano Botti, 5 Antonio Errico, 6 Loredana Sarmati, 7 Fabio Ciceri, 8 Franco Locatelli, 9 Maddalena Giannella, 10 Matteo Bassetti, 11 Carlo Tascini, 12 Letizia Lombardini, 6,13 Ignazio Majolino, 14 Claudio Farina, 15 Francesco Luzzaro, 16 Gian Maria Rossolini, [17][18][19] and …”
Section: F E R R a T A S T O R T I F O U N D A T I O Nunclassified
“…6 Israel experienced a large outbreak beginning in 2006, and efforts to contain this outbreak are continuing. 7,8 Data concerning the epidemiology of CP-CRE remain limited. Several case-control studies have identified healthcare-associated factors as predictors for isolation of CP-CRE among hospitalized patients.…”
mentioning
confidence: 99%